Aktivitas Pemasaran PT. Triartha Cipta Mandiri Dalam Meningkatkan Penjualan Perumahan Granada Rajeg City Tahun 2023 - Syarifah Fatimah; Mochammad Mirza; Alamsyah Alamsyah; Ari Suseno (Lembaga Pengembangan Kinerja Dosen, 2023)
Triartha Cipta Mandiri is a company that operates as a housing developer. PT. Triartha Cipta Mandiri (which is shortened to PT. TCM) moves side by side with PT. Rico Cipta Mandiri is located at Ruko Tangerang City Business Park, D/8, Jl. Raya Jendral Sudirman, Banten. Director of PT. Triartha Cipta Mandiri is Mr. Hamsir Siregar, S.H., M.H. PT. Triartha Cipta Mandiri has been established for 10 years with a Deed of Company Establishment from the Tangerang Regency Notary, Mr. Deni Nugraha, S.E., S.H., M.Kn. dated 25-09-2013 and has received approval from the Minister of Law and Human Rights of the Republic of Indonesia, as stated in his Decree dated 27-09-2013 Number: AHU-50281.AH.01.01 TAHUN 2013. So far, PT. Triartha Cipta Mandiri is expanding its wings in the field of selling subsidized houses. The name of the housing developed by PT. Triartha Cipta Mandiri is Granada Rajeg City which is located in Rajeg District, Tangerang Regency, Banten. Houses that sells by PT. Triartha Cipta Mandiri is a subsidized house by the government with a price of Rp. 168,000,000,- and the houses’ building area of ​​30 M2 and a land area of ​​60 M2. Inside the house there are 2 bedrooms and 1 bathroom. Houses marketing is carried out by deploying several marketing agents. Other than that, to carry out sales and purchases that have been agreed with consumers, PT. Triartha Cipta Mandiri entered into a credit agreement at Bank BTN Syariah. During 2023, house sales have reached 74 houses.